Wann werden Löhne als gerecht eingeschätzt? Eine tauschtheoretische Betrachtung der Lohngerechtigkeit auf dem Arbeitsmarkt - Martin Abraham (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
– The aim of this paper is to analyze why people consider other determinants than performance as important for the evaluation of wage fairness. This question arose from the empirical observation that a considerable proportion of respondents of the Swiss labor market survey reported that one's family situation, education or seniority within the firm should be important for fixing wages. For the analysis of this phenomenon three possible explanations are considered. First people develop a positive attitude towards a distributional rule if they will benefit from this rule. Second the idea of general moral and altruistic norms producing the observed attitudes is discussed. Third an exchange-theory solution is proposed which focuses on balanced exchange processes between the members of a team or a firm. Empirical results clearly support the role of self-interest and exchange processes between team members. However, due to the restricted data only limited evidence for cultural fairness norms could be found.
Keywords: 330; Lohnhöhe; gesellschaftliche Einstellungen; Gerechtigkeit; soziale Normen; Schweiz